Acute phase optical coherence tomography findings in whiplash maculopathy [Whiplash Makulopatinin Akut Evre Optik Koherens Tomografi Bulguları] - (:unkn) unknown (Gazi Eye Foundation, 2020)
Following in-vehicle traffic accident causing whiplash injury, a 52-years old male patient presented with bilateral reduction in visual acuity and loss of central vision. There was diffuse macular edema, thickening at outer retinal segment and subretinal fluid with preserved bilateral foveal pit and inner retinal architecture on optical coherent tomography (OCT). Within 2 weeks following accident, edema was gradually resolved with topical non-steroidal anti-inflammatory treatment and visual improvement was achieved. At the end of the month 3, visual acuity was 20/20 in both eyes and the retinal anatomy was completely normal in OCT. Although whiplash injuries occur commonly after traffic accidents, whiplash maculopathy is extremely rare in the literature due to its denomination. Patients suffer from decreased vision and central scotoma. It has been reported that these retinal changes can be absorbed spontaneously. In our case; similar to previous publications, the pathology is clearly demonstrated. Apart from the others, in our case, findings were recovered with topical NSAI use. © 2019 Gazi Eye Foundation. All rights reserved.
Keywords: Macular edema; Traumatic maculopathy; Whiplash maculopathy